Sci J Hamadan Nurs Midwifery Fac 2018
DOI: 10.30699/sjhnmf.26.a5.323
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Nursing Support From Parents With Meeting the Needs of Mothers of Children Hospitalized in Besat Hospital, Hamadan

Abstract: Introduction: hospitalization of a child is one of the main causes of parent's anxiety. Regarding the importance of providing family-based care, it is necessary for nurses to support and understand parents' needs to provide them. This study aimed to determine the role of nursing support in providing the needs of hospitalized children mothers. Method: This was a descriptive cross-sectional study. 250 mothers of children hospitalized in pediatric ward of Hamadan Besat Hospital, were selected by available method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The first category was missed family-centered care which included three subcategories: poor psychological support, ineffective communication, and training left in the margins. Considering the low level of emotional/psychological support, similar findings were reported by other scholars (28,29) indicating that nurses give the least emotional support to mothers. .…”
Section: Discussionsupporting
confidence: 84%
“…The first category was missed family-centered care which included three subcategories: poor psychological support, ineffective communication, and training left in the margins. Considering the low level of emotional/psychological support, similar findings were reported by other scholars (28,29) indicating that nurses give the least emotional support to mothers. .…”
Section: Discussionsupporting
confidence: 84%
“…2019; 16(4):e92471. meet the comprehensive needs of the child and the family, which forms the basis of the family-centered care (19). The results of this study showed a high level of concern among mothers of hospitalized children.…”
Section: Discussionmentioning
confidence: 70%
“…Credit or value support is used to empower parents to take their parental role. Caring or instrumental support, also called tangible support, includes financial, time, and occupational support, environmental change, or adjustment (19). In determining the aspects of provided support for the parents of hospitalized children, the results of this study showed that the highest support was related to parental validity support and the lowest support was related to caring support.…”
Section: Discussionmentioning
confidence: 89%
“…In a meta-analysis, the third field of support was reported to be emotional support, whereas it was at the lowest level regarding reception ( Almasi et al, 2018 ; Mousavi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, most of these programs began a few days after the infant was admitted to the NICU or following discharge, so they could not help the mother in the first days after birth, especially during the first contact with the newborn infant. Mothers are not always supported emotionally or practically by support systems, especially when needed at the bedside ( Aftyka et al, 2017 ; Almasi et al, 2018 ; Unesi et al, 2017 ; Zavalgard et al, 2017 ) which can cause more stress for family engagement patterns, particularly when mothers are not ready for preterm birth ( Aftyka et al, 2017 ; Mousavi et al, 2016 ). Due to the sensitivity of this era and the lack of appropriate interventions, as a result, it should be the basis of policies and supportive interventions should be strong scientific evidence and maternal preferences and needs.…”
Section: Introductionmentioning
confidence: 99%